McMYB10 Modulates the Expression of a Ubiquitin Ligase, McCOP1 During Leaf Coloration in Crabapple - Li, Ke-Ting; Zhang, Jie; Kang, Yan-Hui; Chen, Meng-Chen; Song, Ting-Ting; Geng, Hui; Tian, Ji; Yao, Yun-Cong (Frontiers in Plant Science, 2018)
In higher plants，anthocyanins are protective secondary metabolites , which contribute to the color of leaves, stems, flowers and fruits, and have been found to have an antioxidant role in human health. In this study, we determined the expression of McMYB10 and its specific E3 ubiquitin ligase, McCOP1, in crabapple leaves during the course of a day and in five leaf development stages. Interestingly, the results showed that the transcription level of McCOP1 genes was higher in daylight than at night, and the transcripts of McMYB10 presented a positive correlation with the transcription of McCOP1-1 and McCOP1-2 and anthocyanin accumulation in a crabapple cultivar with red-colored leaves. Several MYB transcription factor binding sites of the MYBCORE type were found in the McCOP1-1 and McCOP1-2 promoters, and we deduced that there may be a relationship between McMYB10 and McCOP1-1 and McCOP1-2 at the transcriptional level. Yeast one hybrid (Y1H) and electrophoretic mobility shift assays (EMSA) demonstrated that the McMYB10 transcription factor binds specifically to the promoter of McCOP1-1 and McCOP1-2. Furthermore, increased levels of McMYB10 promoted anthocyanin biosynthesis and the expression level of McCOP1-1 and McCOP1-2 in crabapple leaves during continuous light treatments, and overexpression or silencing of McMYB10 in crabapple leaves and apple fruits also result in an increase or decrease, respectively, in the expression of McCOP1-1 and McCOP1-2 and in anthocyanin biosynthesis. Our results reveal a new self-regulation mechanism in where McMYB10 modulates its own expression by activating McCOP1-1 and McCOP1-2 expression to promote ubiquitination of the McMYB10 protein by McCOP1.